Analisis total quality control hasil pengelasan bengkel welding MO & EO PT XYZ menggunakan metode basic seven tools dan new seven tools - Jannaah, Putri Dwi Raudhatul; Winursito, Yekti Condro (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The shipbuilding industry in Indonesia has an important role in supporting the development of the maritime sector as a national priority. PT Analysis using Basic Seven Tools and New Seven Tools shows that spatter has the highest percentage of defects, namely 60%, and there is data with a proportion value of 0.8095 which exceeds the upper control limit (LKA) of 0.7485. The main causes of welding defects include worker errors, less than optimal welding machines, low material quality, inappropriate welding methods, and unfavorable environmental conditions. Therefore, analytical approaches such as control charts and cause-and-effect diagrams are needed to continuously monitor and improve welding quality.